Measuring the Effectiveness of Overlapping Development Activities - Terwiesch, Christian; Loch, Christoph H. (Management Science, 1999)
Overlapping development activities is widely used to reduce project completion times in product development. However, research on the applicability of the concept in different technological environments remains scarce. So far, very few industry-specific studies have statistically confirmed an accelerating effect of overlap. In the present article we statistically measure the effectiveness of overlapping development activities in reducing project completion time. Building on analytical research in operations management, we argue that this effectiveness differs with the organization's capability to resolve uncertainty early in the process. Projects benefit more from overlap if they are able to resolve uncertainty early. This contingency view to overlapping development activities is tested based on data from 140 completed development projects across several global electronics industries.